The Influence Of Innovative Organizational Culture And Employee Support On Team Productivity In Manufacturing Companies - Yani, Silvi; Maryadi, Adi (Review: Journal of Multidisciplinary in Social Sciences, 2025)
This study examines the influence of innovative organizational culture and employee support on team productivity in manufacturing companies. The research uses a quantitative approach by collecting data through questionnaires distributed to employees of manufacturing companies. The analysis uses the SmartPLS method to test the relationship between variables. The results revealed that employee support had a significant positive influence on team productivity, while innovative organizational culture showed a positive but not statistically significant influence. This study shows that human factors, especially in the form of support, motivation, and engagement, play a more decisive role in creating productive teams than organizational culture alone. The findings emphasize the importance of a systemic approach to human resource management, where employee involvement in decision-making, tolerance for experimentation, and opportunities for self-development are key factors in increasing productivity. This research contributes to understanding the dynamics of team productivity and shows that productivity is the result of the complex interaction between organizational culture, support, and individual capacities of employees.